The Spanish Cod Fishing Industry: Radical Production Changes Without Significant Changes in the Innovation System - Manuel González-López (Journal of Entrepreneurship, Management and Innovation)

(untitled)
This paper studies the changes which have occurred in the Spanish cod fishing industry in the last few years. We also aim to understand the dynamics of industrial change and its relation to institutions, understood here as both formal and informal rules and conventions. Our results suggest that sometimes industries, in order to maintain their competitive position, need something more than incremental changes in their products or in the technologies that they use. As we can see with the Spanish cod fishing industry, major changes are needed which affect the institutional set-up of their production system. Nevertheless, even when major changes happen in the production sphere, this does not mean that major alterations happen in the way companies innovate, i.e. in their innovation system.